Alkaloids Production and Cell Growth of Cinchona ledgeriana Moens: Effects of Fungal Filtrate and Methyl Jasmonate Elicitors - Yustiny Andaliza Hasibuan; Diah Ratnadewi; Zainal Alim Mas’ud (Universitas Pendidikan Indonesia, 2021)
Cinchona alkaloids are known as antimalaria and anti-arrhythmic. Due to the long waiting time to harvest, cell culture technology is a challenge. This study aimed to determine the effects of elicitors, filtrate of two strains of endophytic fungi and methyl jasmonate (MeJA), in cell suspension culture of Cinchona ledgeriana on quinine and quinidine production. The cells were cultured for seven weeks in woody plant (WP) media treated with either of those elicitors in various concentrations. The cells growth was observed and the alkaloids were analyzed by HPLC. Cells treated with MeJA failed to grow that led to the cell biomass insufficiency for alkaloids determination. It indicates that the cells are quite sensitive to even low concentration of MeJA that hampered the growth. Cells treated with the filtrate of Diaporthe sp. M13-Millipore filtered (S2M) gave the least cell biomass but presented the highest content of both alkaloids. Diaporthe sp. strain M-13 is stronger as elicitor than M-23 for this plant species. Filtrate of non-virulent fungi can elevate the biosynthesis of alkaloids. This reconfirms that cultured cells are capable to produce secondary metabolites and the productivity can be increased by using an appropriate elicitor.